Interaction of AP-1 with a cluster of NF-kappa B binding elements in the human TNF promoter region. - Udalova, I; Kwiatkowski, D (2001)
Transcriptional activation of the human TNF gene involves multiple regulatory elements whose functional properties vary between stimuli and cell types. Here we have used a COS-7 expression system to dissect the transactivating potential of NF-kappa B binding sites in the human TNF promoter region from other regulatory influences. In this model, NF-kappa B acts largely through a dense cluster of three binding sites located 600 nt upstream of the transcription start site. We show that the transcriptional activity of this complex is highly sensitive to the p65:p50 ratio that is expressed. We demonstrate that the AP-1 complex c-Jun/Fra2 is capable of binding to this region and that this inhibits the transactivating effects of NF-kappa B. These results are suggestive of a complex regulatory element that mediates fine control rather than acting as a simple on-off switch for TNF gene expression.